Three-dimensional numerical investigation of flow and heat transfer characteristics of inline jet arrays - Sezai, I; Aldabbagh, LBY (Taylor & Francis Inc, 2004)
The structure of the flow field and its effect on the heat transfer characteristics of a jet array system are investigated numerically in steady state for Reynolds numbers between 100 and 400. A section of the array consisting of 24 square jets (3 rows x 8 columns) impinging on a heated fiat surface is considered as a representative pattern. The simulations have been carried out for jet-to jet spacings in the range 2D-5D and for nozzle exit-to-plate distances between 0.25D and 2D, where D is the jet width. The results show that the streamwise profile of the Nusselt number exhibits strong periodic oscillations. For small nozzle-to-plate spacings (L-z < D) and low Reynolds numbers, the amplitude of the periodic oscillations is attenuated as one proceeds in the downstream direction. For Re > 100 and L-z greater than or equal to D, secondary peaks are formed downstream as a result of deflection of the jets by the crossflow resulting from upstream jets. The superimposition of the secondary peaks distorts the periodic Nusselt number profile.
Keywords: Rectangular Impinging Jets; Staggered Arrays; Circular Jets; Cross-Flow; Spent Air; Simulation